Communication interventriculaire in a 12-year-old boy as a rare congenital heart disease in Tunis: A case report - Puteri, Aulia Rahman; Denguir, Raouf; Putra, Galih Santoso (Indian Journal of Case Reports, 2025)
Communication interventriculaire, or ventricular septal defect (VSD), is the most common congenital heart malformation in children, accounting for nearly 37% of cases worldwide. While small defects may remain asymptomatic, larger perimembranous defects are frequently associated with significant hemodynamic compromise and progressive valvular dysfunction. We describe the case of a 12-year-old boy with a large perimembranous VSD who presented with recurrent dull, intermittent chest pain, dyspnea, and easy fatigue, symptoms not typically emphasized in pediatric VSD cases. Echocardiography revealed a 5 mm left-to-right shunt (Vmax 4.6 m/s), severe subaortic stenosis due to a subaortic membrane (aortic Vmax 5.4 m/s), and grade II aortic insufficiency. Laboratory tests demonstrated markedly elevated C-reactive protein levels (36.1), indicating systemic inflammation and possible infectious complications. Management included infection control, daily Tansopril therapy, and surgical intervention, with plans for long-term follow-up using echocardiography and laboratory monitoring. When compared with published pediatric cases from Argentina and India, which primarily reported progressive aortic regurgitation and left ventricular outflow tract obstruction, respectively, our case is distinctive due to its initial dominant presentation of chest pain and its strong inflammatory profile. This underscores the heterogeneity of clinical manifestations in VSD and highlights the need for individualized evaluation and treatment strategies to prevent progression and long-term morbidity.